REGULASI EMOSI DAN BURNOUT PADA GURU HONORER SEKOLAH DASAR SWASTA MENENGAH KE BAWAH - DWI KENCANA WULAN; NURMALA SARI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2015)
This study aims to determine the effect of emotional regulation on burnout. This study used quantitative method with psychological scale. There are 77 samples of respondents which are honorary teachers of middle down private elementary school with sampling technique is purposive sampling. This study used two adaptation scales that were burnout and emotion regulation scale. The data processing method that used to examine hypothesis were regression analysis one predictor. Based on the result of data analysis, obtained F count > 18,898 > F table 3,98 with p value = 0,000 (p < 0,05). There is the siginificant effect of emotion regulation on burnout in the honorary teachers of middle down private elementary school. From the equation of regression can be interpretated that if emotional regulation increases one unit, burnout will decrease of 0,425.